Microwave Synthesis of N-Methyl-3-Nó-(1-trizolyl)- 4-substituted Pyrroles - CHAKRAVARTHY AKULA, KALYAN; KANUMALLA, DEEPAKRANTHI (Asian Journal of Chemistry, 2010)
A microwave-enhanced synthesis of N-methyl-3-N'-(1-trizolyl)-4-substituted pyrroles, under solvent free conditions is described. The yields and especially the reaction time are noticeably improved in comparison with conventional heating.